VINCENT: a randomized-controlled trial evaluating venetoclax plus azacitidine versus intensive chemotherapy in patients with newly diagnosed, NPM1-mutated AML - Kretschmer, Lydia; Ruhnke, Leo; Schliemann, Christoph; Fransecky, Lars; Steffen, Björn; Kaufmann, Martin; Burchert, Andreas; Schmid, Christoph; Hanoun, Maher; Sauer, Tim; Metzeler, Klaus H.; Schäfer-Eckart, Kerstin; et al. (Annals of hematology, 2025)
For younger, medically fit patients with NPM1-mutated, FLT3-wildtype acute myeloid leukemia (AML) intensive chemotherapy represents standard of care (SOC), with complete remission (CR) rates observed in up to 85% of patients and 5-year overall survival (OS) rates of 40-50%. However, significant toxicity and need for hospitalization pose challenges on patients’ outcome and quality of life (QoL). Venetoclax (VEN) combined with azacitidine (AZA) has demonstrated encouraging efficacy in older, unfit AML patients, achieving high CR/CRi rates and promising OS with lower toxicity. Prospective, randomized data comparing VEN/AZA to SOC in younger, fit patients are currently missing. VINCENT is a randomized-controlled, multicenter, non-inferiority, phase 2 trial (NCT05904106) evaluating VEN/AZA versus SOC in adults aged 18-70 years with newly diagnosed, NPM1-mutated, FLT3-wildtype AML. Patients medically fit for intensive chemotherapy (ECOG ≤ 2) with adequate organ function are eligible, while patients with relapsed/refractory AML or prior cytotoxic treatment are excluded. A total of 146 patients will be randomized 1:1 to receive either VEN/AZA or SOC. Hematologic remission is evaluated according to ELN 2022 guidelines. The primary endpoint is the modified event-free survival, defined as either primary induction failure, hematologic relapse, molecular failure or death. Secondary endpoints include safety, tolerability, CR/CRi/CRh/CRMRD− rates, MRD kinetics (using NPM1 RT-qPCR and MFC), relapse-free survival, OS, early mortality, health-related QoL and cumulative health-care-resource use. Patients will be followed up for at least two years post enrollment. The VINCENT trial will be the first study to provide comprehensive prospective data comparing VEN/AZA to SOC, addressing both efficacy and patient-centered outcomes.